Pengalaman Kader Kesehatan dalam Meningkatkan Kualitas Kesehatan Keluarga - Mariam Dasat; Dian Anggraini (Journal of Telenursing (JOTING), 2026)
This study aims to provide an overview of the experiences of health volunteers in improving family health quality. A qualitative research design utilizing a phenomenological approach was employed. The findings revealed four themes regarding the volunteers' experiences: family lack of health awareness, refusal to undergo health checks, and the role of family support for volunteer activities. In conclusion, health volunteers serve on the front lines of community service, assisting healthcare professionals in improving family health quality. They encounter various challenges in their work, thereby necessitating both formal and informal support.   Keywords: Health Volunteers, Family Health, Experience, Posyandu for Toddlers, Posyandu for the Elderly